School ties [videorecording (DVD)] - Mandel, Róbert, 1957-; Fraser, Brendan, 1968-; Damon, Matt; Affleck, Ben, 1972-; O'Donnell, Chris (Widescreen DVD collection, 1999)
Set in the 1950s: David Greene, a working-class Jewish quarterback from Scranton, Pennsylvania, is offered a football scholarship to a prestigious New England prep. school. It's David's ticket to an Ivy League education and a way out of his hometown, but there's one condition: the school's elders ask him to be discreet about his religion. At first willing to do so, David struggles with his silence as his popularity grows. David strikes up a friendship with his roommate Chris Reece and a possible romance with Sally Wheeler, a student at a nearby girls' school. But, when David's secret is exposed by a jealous classmate he faces the full force of religious intolerance from the prejudiced White Anglo-Saxon Protestant institution.